Agama dalam Eksistensi Pemahaman Tradisionalis Masyarakat Indonesia: Upaya Membedah Agama Perspektif Tradisional Ekstrem dan Antisipasi Konflik Bermotif Agama - Fikri, Hamdan Khaerul (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2018)
Tradisonalis understanding of the existence of religion in Indonesian society is the construction of understanding religion in General. But in this case the starting point of the religious community's understanding of Indonesia which is still very traditional in interpreting religion, then there can be remove so just with the current development of modernity that continues to evolve. See the textual basis of religion that is the hallmark of the Indonesian community, why not, because the large number of religious understanding traditionally make the society tend to think that many radical and fundamental cause of disputes between fellow human beings was no exception non islam in Indonesia also became the target of the current religiousmodernity also potentially give rise to religious understanding textual basis in the application seharai the days thus the author trying to browse understanding religion in a society traditionally Indonesia in various pespektif like the socio cultural, economic and political as the base material in the writing of this.